THE ADDED VALUE AND PROFIT ANALYSIS OF CITRONELLA ESSENTIAL AND AROMATHERAPY OIL IN KPH REGION XIII LAKITAN-BUKIT COGONG - Yunita Yunita; Trissa Silvian; Thirtawati Thirtawati (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2024)
The processing of citronella into essential oil will result in added value to the citronella. KPH Region XIII Lakitan-Bukit Cogong also utilizes the opportunities available by making derivative products of citronella essential oil as a base for making aromatherapy oil. The purpose of this study was to find out how much profit is obtained and to analyze the added value of citronella essential and aromatherapy oil agroindustry in KPH Region XIII Lakitan-Bukit Cogong. The method used in this study are profit analysis and the calculation of added value using Hayami Modification Method. The results obtained in this study were the amount of profit obtained from the agroindustry of citronella essential and aromatherapy oils is 115,285,050 IDR. The added value ratio by processing citronella into citronella essential oil was 41,20% and by processing of citronella into aromatherapy oil was 72.14%. Both of these value-added ratios exceed 40% and were included in the high category.